National identity as the basis for shaping patriotism in Poland - Kamil Roman (Kazimierz Wielki University, 2018)
The identity category is a crucial term describing the political and cultural relationships that occur within a given population. Identity is also a primary term for studying the essence of patriotism. This article attempts to analyze the impact of national identity on shaping patriotic attitudes, attachment to the homeland and civic activity. The publication also contains an overview of the applied solutions in Poland in the area of shaping awareness and national identity of Poles.